Novel insights into rural spatial design: A bio-behavioral study employing eye-tracking and electrocardiography measures - Minqi Shi; Ruili Wang; Lei Zhang (PLoS ONE, 2025)
In order to objectively assess the effectiveness of rural space design on the affective dimension, this study utilized eye-tracking and electrocardiogram (ECG) monitoring techniques to quantify users’ visual attention and emotional responses and to assess the impact of rural design on users’ affective experience. The results show that incorporating natural elements and cultural features into the design enhances the values of the subjects’ pupil diameter change rate, Heart Rate Variability Index (HRV), subjective evaluation and reduces their Saccade Velocity Average. The experimental results not only verify the application value of eye tracking and ECG monitoring techniques in assessing the design effect of rural space, but also provide a scientific assessment method based on the user’s physiological and emotional responses, thus providing a strong support for the optimization of rural space design.